A century of air power : the changing face of air warfare 1912-2012 - Sloggett, Dave (Pen and Sword, 2013)
No other technical development since the introduction of gunpowder has had as great an influence on warfare as the aircraft. From its early beginnings as simply a means of aerial reconnaissance to its utter supremacy on the battlefield, the aircraft has evolved into the most versatile and precise killing machine known to man. In this wide-ranging and comprehensive study, David Sloggett, an internationally-respected defence analyst, investigates the changing role and increasing significance of air power over the course of the previous 100 years. This is accomplished by detailing every major con.